A qualitative study of communication management to stabilize the hospitality staff performance in the digital age - Haura Tabriza Asyan; Izza Ulumuddin Ahmad Asshofi (Surya Hijau Manfaat, 2026)
The tourism industry has many components that are needed to meet the needs of tourists and face globalization. In facing the dynamics of globalization that affect the work system in the tourism industry, especially hospitality, an understanding of effective communication is a key factor in maintaining smooth operations and adapting to change, especially in the digital age. The emergence of misunderstandings of the work system, poor communication between departments through the hotel's digital system, and poor staff relations can affect the internal performance of the hotel. This can lead to data entry errors, delays in interdepartmental work, and disharmony in the work environment. This study applies a qualitative method through participant observation. The purpose of this research is to examine the understanding and delivery of communication between hotel staff in the context of digital transformation and its impact on staff harmony and staff attitudes towards guests. In addition, it provides an understanding of communication between hotel staff to stabilize the hotel internally. The main contribution of this study is the recommendation of structured communication standards as a practical guide for hotel management, helping stabilize staff performance and significantly improving overall service quality.